Computer-assisted Follow-up Register for the North-East of Scotland. Issue 5695 (28th February 1970) - Hedley, Anthony J.; Scott, Anne M.; Weir, R. Deans; Crooks, James
Abstract : An automated follow-up register for the detection of iatrogenic thyroid disease has been established as a joint venture between the general practitioners in the north-east of Scotland and the thyroid clinic of Aberdeen General Hospitals. The data-processing operations in the system are handled by an International Computers Limited 4/50 computer. Patients are followed up at predetermined intervals and the system has been designed to process, screen, and store clinical and biochemical follow-up data and report results to the patients, general practitioners, and the hospital records department.